The Relationship of Advertising and Service Quality to The Brand Equity of Midnight Sun in Jakarta - Iriandari, Gladista Galuh; Hudrasyah, Herry (Journal of Business and Management, 2015)
Abstract. This study aimed to analyze the influence of advertising and the quality of service to brand equity in the Midnight Sun in Jakarta. The method used is descriptive quantitative analysis with correlational analysis approach. The model in question is the relationship between the dependent variable with independent variables, using multiple regression models with ordinal data. Ordinal data compiled based on Likert scale. The dependent variable is the brand equity (Y) and the independent variables are advertising (X1) and quality of service (X2). Place of this research done in Midnight Sun Jakarta by using a sample of 75 people and the determination of the sample using simple random sampling technique.The results showed that advertising has a significant impact on the brand equity of Midnight Sun. Service quality significantly impacts on the brand equity of Midnight Sun. Service quality is more dominant than advertising on brand quity of Midnight Sun.Based on the results of multiple regression test found the coefficient of determination (R Square) of 0.814. This means that the independent variable (advertising and quality of service) contribute to dependent variable (brand equity) amounted to 81.4% while the remaining 18.6% is influenced by other factors not examined, such as product quality, price policy, the business location and so on.Ã‚Â Keywords: Advertising, Service Quality and Brand Equity.